CAD Algorithm for Automated Selection of the Battery Capacity in the Substation Operational DC System - Panova, E.A.; Varganova, A.V.; Sorokin, N.S. (2020 International Multi-Conference on Industrial Engineering and Modern Technologies (FarEastCon), 2020)
The DC operating current system at the substation is an element that ensures not only the uninterrupted operation of the facility itself, but also the entire section of the power system. Therefore, high requirements are imposed on its design in terms of reliability. The project of a direct current system is associated with the need for the designer to work with a large volume of regulatory and technical documentation, as well as to perform a significant amount of the same type of routine calculations. It is advisable to solve this problem using CAD. The paper proposes an algorithm for the automated determination of the required battery capacity for the designed substation. The algorithm is based on the requirements of the current design standards and allows use the adopted design solutions as initial data at the stages of selecting switchgear circuits and electrical apparatus for them. In addition, the proposed CAD system allows the designer to use the built-in database of electrical devices, which greatly simplifies the design of an electrical installation. The work is carried out with the financial support of a grant from the President of the Russian Federation for young scientists - candidates of sciences MK-939.2019.8.